2017
DOI: 10.1186/s12864-017-3791-6
|View full text |Cite
|
Sign up to set email alerts
|

A reference genome for Nicotiana tabacum enables map-based cloning of homeologous loci implicated in nitrogen utilization efficiency

Abstract: BackgroundTobacco (Nicotiana tabacum) is an important plant model system that has played a key role in the early development of molecular plant biology. The tobacco genome is large and its characterisation challenging because it is an allotetraploid, likely arising from hybridisation between diploid N. sylvestris and N. tomentosiformis ancestors. A draft assembly was recently published for N. tabacum, but because of the aforementioned genome complexities it was of limited utility due to a high level of fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
309
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(323 citation statements)
references
References 62 publications
9
309
1
4
Order By: Relevance
“…). The Blast function available on the Sol Genomics Network server (https://solgenomics.net/) (Edwards et al , ) showed a localization of the eIF4E‐2, 3 and 4 genes on chromosome 14 of the tobacco genotype K326 (PI552505), starting, respectively, at positions 109418388, 109399608 and 109292645, indicating these genes are located within a ca. 132 kbp region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…). The Blast function available on the Sol Genomics Network server (https://solgenomics.net/) (Edwards et al , ) showed a localization of the eIF4E‐2, 3 and 4 genes on chromosome 14 of the tobacco genotype K326 (PI552505), starting, respectively, at positions 109418388, 109399608 and 109292645, indicating these genes are located within a ca. 132 kbp region (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The (draft) genome sequences of a number of plant species with glandular trichomes are now available. A nonexhaustive list includes different tomato species (Solanum lycopersicum and Solanum pimpinellifolium [Tomato Genome Consortium, 2012] and Solanum pennellii [Bolger et al, 2014]), potato (Solanum tuberosum [Xu et al, 2011]), cucumber (Cucumis sativus [Huang et al, 2009]), tobacco (Nicotiana tabacum [Sierro et al, 2014;Edwards et al, 2017]) and its related species (Nicotiana sylvestris and Nicotiana tomentosiformis [Sierro et al, 2013]), hot pepper (Capsicum annuum ), mint (Mentha longifolia [Vining et al, 2017]), cannabis (Cannabis sativa [van Bakel et al, 2011]), and hop (Humulus lupulus [Natsume et al, 2015]). …”
Section: A Detailed Understanding Of Glandular Trichome Initiation Anmentioning
confidence: 99%
“…Nitrogen fertilizer application in burley tobacco is normally 4–5 fold higher than other tobacco types to produce the same levels of biomass, which resulted in low nitrogen use efficiency and more than 100 times higher of nitrate content in burley tobacco, further contributing to much more TSNA formation during both leaf curing and storage 2,3 . Transcriptomic analysis showed that expression of genes involved in photosynthesis were decreased by reducing nitrogen application, resulting in decreased leaf biomass accumulation and carbohydrates formation in burley tobacco 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate is largely accumulated and carbohydrates are extremely low in burley tobacco, which are associated with one double recessive genes mutation 2 . In this study, nitrate content was significantly decreased and leaf biomass was significantly increased by spraying glycerol ( P  < 0.01), and the effect of 20% nitrogen reduction with spraying glycerol was the most effective in decreasing nitrate content in burley tobacco seedlings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation